¡Alerta! Engineering on Shaky Ground - Reddy, Elizabeth (Engineering Studies, 2023)
A lively account of a controversial technology developed to mitigate earthquake risk and change how we live with threatening environments.The Sistema de Alerta Sísmica Mexicano is the world's oldest public earthquake early warning system. Given the unpredictability of earthquakes, the technology was designed to give the people of Mexico City more than a minute to prepare before the next big quake hits. How does this kind of environmental monitoring technology get built in the first place? How does its life-saving promise align with reality? And who shapes modern risk mitigation? In ¡Alerta!, Elizabeth Reddy surveys this innovation to shed light on what it means to imagine a world where sirens could sound out an ¡alerta sísmica! at any moment-and what it would be like to live in such a world.Proponents of earthquake early warnings havelong held that the technology can save lives and limit economic losses. Drawing on ethnographic fieldwork and archival data, Reddy conducts a thorough, qualitative analysis of these claims and considers the requirements and uses of the alert system. She embeds her study in a rich narrative of the engineers who designed the system in conjunction with contingent political and environmental conditions. The result demonstrates how addressing earthquake dangers is no small task: it means trying to change relationships between the environment, society, and technology. Doing so, she critiques universalist and techno-centric approaches to hazard risk mitigation and celebrates the potential of contextually appropriate and broadly supported efforts.¡Alerta! takes readers on a vivid journey into the world of Mexican earthquake risk mitigation, with critical insights for anthropologists and science and technology studies scholars, as well as specialists in the geosciences, engineering, and emergency management.